High-temperature stress during drying improves subsequent rice (Oryza sativa L.) seed longevity - Whitehouse, Katherine J.; Hay, Fiona R.; Ellis, Richard H. (Cambridge University Press, 2017)
Post-harvest drying prolongs seed survival in air-dry storage; previous research has shown a benefit of drying moist rice seeds at temperatures greater than recommended for genebanks (5–20°C). The aim of this study was to determine whether there is a temperature limit for safely drying rice seeds, and to explore whether the benefit to longevity is caused by high-temperature stress or continued seed development. Seeds of two rice varieties were harvested at different stages of development and dried initially either over silica gel, or intermittently (8 h day–1) or continuously (24 h day–1) over MgCl2 at temperatures between 15 and 60°C for up to 3 days. Seeds dried more rapidly the warmer the temperature. Subsequent seed longevity in hermetic storage (45°C and 10.9% moisture content) was substantially improved by increase in drying temperature up to 45°C in both cultivars, and also with further increase from 45 to 60°C in cv. ‘Macassane’. The benefit of high-temperature drying to subsequent longevity tended to diminish the later the stage of development at seed harvest. Intermittent or continuous drying at high temperatures provided broadly similar improvements to longevity, but with the greatest improvements detected in a few treatment combinations with continuous drying. Heated-air drying of rice seeds harvested before maturity improved their subsequent storage longevity by more than that which occurred during subsequent development in planta, which may have resulted from the triggering of protection mechanisms in response to high-temperature stress.